The Impact of Rapid Aging and Pension Reform on Savings and the Labor Supply - He, Hui (IMF Working Papers; Working Paper ;, 2019)
We study, both empirically and quantitatively, the role of savings and the labor supply in self-insurance channels over the life cycle when one faces not only idiosyncratic income risks, but also changes in longevity risk and pension benefits. We pick China as a case study since China has undergone a dramatic process of rapid aging and a tremendous reduction in social security benefits for the period 1995-2009. We find that both savings and the labor supply are quantitatively important self-insurance channels in responding to changes in longevity risk and pension benefits, and the responses via adjustment to savings and labor supply have significant macroeconomic implications. Applying the model to China, we find that the pension reform and rapid aging together contribute 55 percent of the increase in the household saving rate from 1995 to 2009, and they jointly capture about 64 percent of the drastic increase in the labor supply for the same period.